Adaptations of the News Media and Social Media Logics by Indonesian Political Parties’ Leaders and Presidential Candidates after 2004 Indonesian Presidential Election - Nyarwi Ahmad (Ikatan Sarjana Komunikasi Indonesia, 2022)
Adaptations of political actors and organizations in Asian democratic countries to the media and social media logics have been increasingly visible. This article is specified to answer the following questions of how Indonesian political parties’ leaders and presidential candidates after 2004 Indonesian presidential election adapted to the news and social media logics and what drove such adaptations. Focusing on such questions, this article adopts theoretical models of mediatisation of politics formulated by Mazzoleni and Schulz, Strömbäck and Stromback and Van Aelts and extracts in-depth interview data derived from six Indonesian political parties’ leaders, two political consultants and six senior journalists associated with Indonesian media using the qualitative content and thematic analyses. The findings are as follows. These political parties’ leaders and presidential candidates favoured adapting to the news and social media logics when they got to deal with political issues and affairs, formulate political policies and secure their personal images in Indonesian political sphere. Such development was driven by the following factors, including establishing democratic political and media systems, increasing the roles of the media as sources of political information, escalating freedoms of Indonesian media and journalists to manage the media logic. Theoretical implications are chronicled and research recommendations are displayed.